2013
DOI: 10.1016/j.crohns.2012.06.011
|View full text |Cite
|
Sign up to set email alerts
|

The risk of lymphoma and immunomodulators in patients with inflammatory bowel diseases: Results from a population-based cohort in Eastern Europe

Abstract: Background and aims: Prior studies suggest a small but significantly increased risk of lymphoma in adults with inflammatory bowel disease (IBD), especially in patients treated with thiopurines. No data was available from Eastern Europe. The aim of this study was to analyze the incidence of lymphomas as related to drug exposure, in a population-based Veszprem province database, which included incident cases diagnosed between January 1, 1977 and December 31, 2008. Methods: Data from 1420 incident patients were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 35 publications
0
15
0
1
Order By: Relevance
“…adalimumab and certolizumab) and more recent data 20,21 suggests that there may be legitimate safety concerns related to immunomodulator use to consider before using combination therapy. 22 Subjects in SONIC were naive to both IM and anti-TNF therapy and most had a short disease duration.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…adalimumab and certolizumab) and more recent data 20,21 suggests that there may be legitimate safety concerns related to immunomodulator use to consider before using combination therapy. 22 Subjects in SONIC were naive to both IM and anti-TNF therapy and most had a short disease duration.…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Most population-based studies indicate a risk similar to that of the general population, with one recent study giving an absolute incidence rate of 1.55/10 000 patient-years and a standardised incidence ratio (SIR) of 1.37 (95% CI 0.44 to 4.26) 1. Furthermore, the severity of the disease is not thought to confer an increased risk, unlike in rheumatoid arthritis patients where chronic active inflammation is associated with a higher incidence of lymphoma 5…”
Section: Discussionmentioning
confidence: 99%
“…90 Recent population cohort studies have assessed the risk of lymphoma in patients with IBD. 88,[91][92][93][94][95][96] A nationwide Dutch study did not suggest any overall significantly increased risk for lymphoma in IBD patients, 96 whereas 3 French studies and a large nested, controlled study using the United Kingdom General Practice Research Database demonstrated an increased risk of developing lymphoproliferative disorders among patients treated with thiopurines for IBD. [92][93][94][95] Whether this association is causal or it is the inflammation that thiopurines are used to diminish that actually causes the lymphoproliferative disorders has not yet been determined, but the available data add further weight to the argument that the benefits of thiopurines used in IBD greatly outweigh their risks.…”
Section: Malignant Complicationsmentioning
confidence: 99%
“…Recent population cohort studies have assessed the risk of lymphoma in patients with IBD . A nationwide Dutch study did not suggest any overall significantly increased risk for lymphoma in IBD patients, whereas 3 French studies and a large nested, controlled study using the United Kingdom General Practice Research Database demonstrated an increased risk of developing lymphoproliferative disorders among patients treated with thiopurines for IBD .…”
Section: Malignant Complicationsmentioning
confidence: 99%